Happy Easter from the crayons - Daywalt, Drew; Jeffers, Oliver (New York : Philomel, an imprint of Penguin Random House LLC, 2023)
"Easter is the perfect holiday for crayons! They get to learn new shapes and decorate one giant egg together$1! =(Bbut where will they hide it?! Blue Crayon has some ideas$1! =(B" --publisher's website.s
Ages 4-8.
AD320L
Decoding demand: 66 (high) Semantic demand: 48 (medium) Syntactic demand: 35 (low) Structure demand: 63 (high)
Keywords: Crayons -- Juvenile fiction; Color -- Juvenile fiction; Shapes -- Juvenile fiction; Easter eggs -- Juvenile fiction; Easter egg hunts -- Juvenile fiction; Hiding places -- Juvenile fiction; Picture books; Easter stories; Easter fiction; Picture books